Library- park purpose as potencializer and renewal of a public space - Camacho Maurad, Guissella Solange (2021)
The public space is a transforming and renew urban axis within the cities, which not only beautify the urban landscape, but also connect social, cultural and economic activities. The purpose of this project is to design a Library Park to give a cultural, social and economic space to inhabitants in an empty terrain located in Machala´s city, from El Oro province in the Ecuador’s south. It is placed which is near to the jail, it has been abandoned in the hub, becoming a difficult connectivity inside the city. For that reason, is proposed the creation of a connectivity between close infrastructure and the improving population cultural and educational activities. Moreover, taking advantage of the recognition of the Christmas Tree popularity, as the tallest of the country, locating it in the sunbelt of the plaza in order to attract more tourists, and give it its own place as well. The proposal is linked with the results got by surveys to close community with the purpose to design spaces which are according to user´s needs.